"For Me, This Has Been Transforming": A Qualitative Analysis of Interprofessional Relationship-Centered Communication Skills Training. (December 2020) - Hirschmann, Krista; Rosler, Greta; Fortin VI, Auguste H
In 2018, Yale Medicine (YM)—an academic multispecialty practice—and Yale New Haven Health System (YNHH), partnered with the Academy of Communication in Healthcare to develop a one-day interprofessional workshop to introduce relationship-centered communication skills to all of their nurses and physicians. Relationship-centered communication skills include showing positive regard, listening actively and expressing empathy and have been demonstrated to improve patient outcomes. A professionally diverse group of 12 nurses and physicians, committed to improving patient experiences, were purposefully selected for training to teach the workshop. Individual interviews with trainers 3 months post training revealed themes reflecting the intrapersonal, interpersonal, and organizational impact of participation in the Train-the-Trainer program. At the intrapersonal level, training contributed to personal growth, skillfulness, and confidence. At the interpersonal level, it expanded and strengthened professional networks. As an organizational catalyst, training transformed the work experience among nurse and physician trainers, thereby supporting YM/YNHH's vision to provide interprofessional relationship-centered care. Results suggest that trainer training had additional benefits beyond learning to deliver the workshop, including improving the quality of trainers' personal and professional relationships, and enhancing organizational efficiency and interprofessionalism.